Hydrological modelling for reservoir operation: application of SWAT Model for Kalu Ganga Catchment, Sri Lanka - Madushanka, G. A. T.; Nandalal, K. D. W.; Muthuwatta, Lal P. (Sri Lanka Journals Online, 2022)
Kalu Ganga, a major tributary of Amban Ganga, is one of the perennial rivers of Sri Lanka. Also, Amban Ganga is a major tributary of Mahaweli Ganga. The Kalu Ganga starts from Knuckles mountains, and about 90% of the catchment is covered with forests. The Government of Sri Lanka constructed Kalu Ganga and Moragahakanda Reservoirs in 2014 to increase the water availability in Mahaweli Basin to improve the agricultural and drinking water benefits in several provinces. This study used the Soil Water Assessment Tool (SWAT) to simulate the hydrology of the Kalu Ganga catchment and estimate the daily streamflow series of the Kalu Ganga. The long-term mean annual flow of the Kalu Ganga at the dam site would be 196 MCM (equivalent to 6.24 m3/s) with a standard deviation of 57.5 MCM and coefficient of variation of 0.29. The mean annual catchment rainfall is 2763 mm, streamflow is 59%, and evapotranspiration is 33% of the rainfall. The Kalu Ganga catchment hydrology is dominated by the wet season rainfall, which governs the Kalu Ganga flow, where 89% of the annual flow volume is produced. Further, 67% of the flow volume is produced from November to January. The model results show that 89% of the annual average of streamflow is generated as baseflow, a feature of a perennial river. The high baseflow fraction is hydrologically favourable for the water availability of the catchment as this shows the utilizable quantity of water is high.